2007
DOI: 10.1107/s1600536807000323
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Bis(2-phenylethyl)thiourea

Abstract: Key indicatorsSingle-crystal X-ray study T = 173 K Mean (C-C) = 0.003 Å R factor = 0.042 wR factor = 0.100 Data-to-parameter ratio = 19.5For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Such a situation is unexpected, since for previously X-ray characterized chiral and non-chiral homosubstituted thioureas, onedimensional supramolecular structures based on C═S•••H-N hydrogen bonds are predominant, providing that the thiourea is in a ZZ conformation (e.g. Vázquez et al, 2004;Custelcean et al, 2005;Shashidhar et al, 2006;Sadiq-ur-Rehman et al, 2007). Instead, the crystal structure of the title compound is determined by weak N-H…”
Section: Sup-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a situation is unexpected, since for previously X-ray characterized chiral and non-chiral homosubstituted thioureas, onedimensional supramolecular structures based on C═S•••H-N hydrogen bonds are predominant, providing that the thiourea is in a ZZ conformation (e.g. Vázquez et al, 2004;Custelcean et al, 2005;Shashidhar et al, 2006;Sadiq-ur-Rehman et al, 2007). Instead, the crystal structure of the title compound is determined by weak N-H…”
Section: Sup-1mentioning
confidence: 99%
“…For C 2 homosubstituted thioureas, see: Bailey et al (1997); Lai & Tiekink (2002). For common hydrogen-bonding schemes in thioureas, see: Vá zquez et al (2004); Custelcean et al (2005); Shashidhar et al (2006);Sadiq-ur-Rehman et al (2007); Saxena & Pike (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…Among organotin(IV) compounds, organotin(IV) carboxylates have been studied extensively for their antimicrobial, antiinflammatory and antituberculosis activities 5 . In view of well known application and biological activities of organotin derivatives we are continuously involved in synthesis and characterization of organotin(IV) carboxylates [6][7][8] .Recently, we have investigated organotin compounds containing alkoxide ligand 4-hydroxypiperidine with di-and triorganotin moieties and the result of this study are reported here in.…”
mentioning
confidence: 99%
“…Among organotin(IV) compounds, organotin(IV) carboxylates have been studied extensively for their antimicrobial, antiinflammatory and antituberculosis activities 5 . In view of well known application and biological activities of organotin derivatives we are continuously involved in synthesis and characterization of organotin(IV) carboxylates [6][7][8] .…”
mentioning
confidence: 99%